Palimpsest Sin. ar. NF 66: Presentation and Translation - Pitt, Rafael César (Revista Archai, 2025)
This work has two objectives: to present a recent source on Orphism and to translate the Greek text into Portuguese. The Palimpsest Sin. ar. NF 66 shows two mythical narratives involving the young god Dionysus, the attempt to remove him from Zeus' throne, and a rare dialogue between Aphrodite and Persephone. The condition of the original document and clues in its content suggest ancient origins and relevance to the field of Orphic studies.